Misconceptions and Barriers to the Use of Hypertonic Saline to Treat Hyponatremic Encephalopathy - Ayus, Juan Carlos; Moritz, Michael L. (Frontiers in Medicine, 2019)
Hyponatremic encephalopathy is a potentially life-threatening condition with a high associated morbidity and mortality. It can be difficult to diagnose as the presenting symptoms can be non-specific and do not always correlate with the degree of hyponatremia. It can rapidly progress leading to death from transtentorial herniation. Hypertonic saline is the recommended treatment for hyponatremic encephalopathy, yet it is infrequently used. We believe that the main barriers to its use is the perception that hypertonic saline is associated with a significant risk for cerebral demyelination, that it can’t be administered through a peripheral IV and that it requires monitoring in the ICU. Two illustrative cases are presented followed by a discussion of how intermittent bolus’s of 100 – 150 ml of 3% NaCl in rapid succession to acutely increase the plasma sodium by 4 – 6 mEq/L is a safe and effective way to treat hyponatremic encephalopathy, that can be administered through a peripheral IV in a non-ICU setting.